Targeting NF-κB-mediated inflammatory pathways in cisplatin-resistant NSCLC. (September 2019) - Ryan, Sarah-Louise; Beard, Sam; Barr, Martin P.; Umezawa, Kazou; Heavey, Susan; Godwin, Peter; Gray, Steven G.; Cormican, David; Finn, Stephen P.; Gately, Kathy A.; Davies, Anthony M.; Thompson, Erik W.; et al.
Highlights: Altered NF-ĸB expression was evident in cisplatin-resistant versus cisplatin-sensitive NSCLC cells. The NF-κB inhibitor, DHMEQ, counteracted a cisplatin-mediated increase in NF-κB expression. DHMEQ treatment enhanced the sensitivity of cisplatin-resistant NSCLC cells to cisplatin in vitro . Abstract: Objectives: The majority of patients with non-small cell lung cancer (NSCLC) present with advanced stage disease, at which time chemotherapy is usually the most common treatment option. While somewhat effective, patients treated with platinum-based regimens will eventually develop resistance, with others presenting with intrinsic resistance. Multiple pathways have been implicated in chemo-resistance, however the critical underlying mechanisms have yet to be elucidated. The aim of this project was to determine the role of inflammatory mediators in cisplatin-resistance in NSCLC. Materials and methods: Inflammatory mediator, NF-κB, and its associated pathways were investigated in an isogenic model of cisplatin-resistant NSCLC using age-matched parental (PT) and corresponding cisplatin-resistant (CisR) sublines. Pathways were assessed using mass spectrometry, western blot analysis and qRT-PCR. The cisplatin sensitizing potential of an NF-κB small molecule inhibitor, DHMEQ, was also assessed by means of viability assays and western blot analysis. Results: Proteomic analysis identified dysregulated NF-κB responsive targets in CisR cells when compared to PT cells, with increased NF-κB expression identified in four out of the five NSCLC sub-types examined (CisR versus PT). DHMEQ treatment resulted in reduced NF-κB expression in the presence of cisplatin, and re-sensitized CisR cells to the cytotoxic effects of the drug. Conclusion: This study identified NF-ĸB as a potential therapeutic target in cisplatin-resistant NSCLC. Furthermore, inhibition of NF-ĸB using DHMEQ re-sensitized chemo-resistant cells to cisplatin treatment.